All options on the table : leaders, preventive war, and nuclear proliferation - Whitlark, Rachel Elizabeth (Cornell University Press, 2021)
"This book uses archivally based, comparative case studies to explore decision making regarding preventive war as a counterproliferation strategy by (1) US presidents Kennedy, Johnson, Bush 41, Clinton, and Bush 43 against China, Iraq, and North Korea and (2) Israeli prime ministers Begin, Rabin, and Olmert against Iraq, Pakistan, and Syria"-- Provided by publisher
Keywords: Preemptive attack (Military science) -- Case studies.; Nuclear arms control.; Deterrence (Strategy); International relations -- History -- 20th century.; International relations -- History -- 21st century.; Attaque préventive (Science militaire) -- Études de cas.; Armes nucléaires -- Contrôle.; Dissuasion (Stratégie); POLITICAL SCIENCE / Public Policy / Social Security; International relations; Nuclear arms control; Preemptive attack (Military science); 1900-2099; Electronic books.; Case studies; History